PECULIARITIES OF THE EMOTIONAL STATES OF SERVICEMEN OF THE NEW DRAFT DURING THE ADAPTATION PERIOD - Дубчак, О.; Караульщук, Л. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article focuses on the problem of adaptation of servicemen of the new draft and the features of their emotional states. The conscription and military service "is a powerful psycho-emotional factor" that affects the mentality and makes the individual adapt to new conditions of life. Military service is an important but difficult (often extreme) stage of personal development. The overwhelming majority of servicemen immediately begin to feel subjective discomfort, emotional suppression or stress; they show signs of increased anxiety and some poor mental agility. The article determines that with the presence of various character accentuations, emotional-volitional or neuropsychic instability, undeveloped ability to self-regulation of psychophysiological states, the influence of stressful factors can lead to disruption of regulatory mechanisms, maladaptive behavior of a military man. Neuropsychic instability of serviceman is thought to be as the inability of an individual to maintain mental capacity, an adequate level of neuro-emotional stress, which corresponds to the activity performed, the stability of mental functions under the influence of stressful factors. Most neuropsychic disorders in young servicemen are adaptable, that is, due to the difficulties of their adaptation to the new conditions of life and activity peculiar to military service. Adaptation is the process of assimilation by young soldiers of their social roles, service and social functions, and their inclusion in the system of personal contacts and relations. Thus, in the structural diagram of the adaptation process, three main areas can be distinguished: 1) mastering of official job functions; 2) inclusion in the public life of the collectivity; 3) the establishment of interpersonal, friendships and relationships.